Trade and wages in Colombia - Robbins, Donald (Estudios de Economía, 2016)
This paper examines the impacts of real devaluation, trade liberalization and the growing relative supply of skill on wage dispersion in Colombia’s seven principal cities over 1976-1994. The Hecksher-Ohlin-Samuelson (HOS) framework predicts that while labor supply shifts and devaluation should not affect wage dispersion, trade liberalization should compress wages in LDC’s. My findings differ: growth in the supply of skills lowers, and liberalization and real devaluation raise, wage dispersion. This is not due to failure of the HOS assumptions of factor-diversified trade or that Colombia is skilled relative to the world average. The data are consistent with non-HOS assumptions where devaluation and liberalization encourage capital and embodied technical flows.